The Effect of Psycho-Social Problems on Risky Behaviors in People Living With HIV in Tehran, Iran - Mehrnaz Rasoolinejad; Nasrin Abedinia; Ahmad Ali Noorbala; Minoo Mohraz; Zahra Bayat Jozani; Banafsheh Moradmand Badie (Tehran University of Medical Sciences, 2018)
Objective: Over the past years, the prevalence and the progression rate of HIV infection in Iran especially through high-risk sexual relationships have regrettably been reported at very high levels. This cross-sectional study tries to analyze stigma, mental health, and coping skills on risky behaviors in HIV-positive adults in Tehran- Iran. Materials and methods: This cross-sectional study was conducted on a sample of 450 HIV-positive adults. Participants completed a socio-demographic questionnaire, the General HealthQuestionnaire-28, the Berger HIV Stigma Scale as well as the Lazarus Ways of Coping Questionnaire (WOCQ). To analyze the data, the independent-samples t-test and Pearson Correlation were used. Results: The findings of this study revealed that mental health, stigma, and avoidance-escape coping mechanisms were correlated with risky behaviors (p ˂ 0.05).Furthermore, the amount of stigma among female individuals compared to men was reported at higher levels and mental health status in the given group was lower than among male individuals. Conclusion: It seems that psychological treatment techniques could be effective in improving mental health and reducing risky behaviors.